Total surface area is 152 cm
The first step to solving this is to use tan(t) =
![\frac{sin(t)}{cos(t)}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsin%28t%29%7D%7Bcos%28t%29%7D%20)
to transform this expression.
cos(x) ×
![( \frac{sin(x)}{cos(x)} + cot(x) )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Bsin%28x%29%7D%7Bcos%28x%29%7D%20%2B%20cot%28x%29%20%29)
Using cot(t) =
![\frac{cos(x)}{sin(x)}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bcos%28x%29%7D%7Bsin%28x%29%7D%20)
,, transform the expression again.
cos(x) ×
![( \frac{sin(x)}{cos(x)} + \frac{cos(x)}{sin(x)} )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Bsin%28x%29%7D%7Bcos%28x%29%7D%20%2B%20%20%5Cfrac%7Bcos%28x%29%7D%7Bsin%28x%29%7D%20%29)
Next you need to write all numerators above the least common denominator (cos(x)sin(x)).
cos(x) ×
![\frac{sin(x)^{2} + cos(x)^{2} }{cos(x)sin(x)}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsin%28x%29%5E%7B2%7D%20%2B%20cos%28x%29%5E%7B2%7D%20%20%7D%7Bcos%28x%29sin%28x%29%7D%20)
Using sin(t)² + cos(t)² = 1,, simplify the expression.
cos(x) ×
![\frac{1}{cos(x)sin(x)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bcos%28x%29sin%28x%29%7D%20)
Reduce the expression with cos(x).
![\frac{1}{sin(x)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bsin%28x%29%7D%20)
Lastly,, use
![\frac{1}{sin(t)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bsin%28t%29%7D%20)
= csc(t) to transform the expression and find your final answer.
csc(x)
This means that the final answer to this expression is csc(x).
Let me know if you have any further questions.
:)
Answer:
3/4
Step-by-step explanation:
(17,-7) And (13,-4). First take -4 and subtract it from-7. When you do that you get 3. Then Subtract 13-17. You get 4. Write 3 and 4 as a fraction. 3/4. The 3 is the x-value and the 4 is the y value. So 3/4 is your slope
The answer should be C. y=-3x+7
use the formula y=mx+b where mx is the slope and b is the y-intercept.
in this case, the slope is decreasing by 3 so -3 would fit in for mx. if you look on the y-int you’ll see that the value is positive 7.
when you put this together, you’d get the equation y=-3x+7
hope this helps.